2021
DOI: 10.1002/dev.22176
|View full text |Cite
|
Sign up to set email alerts
|

High vagal tone and rapid extinction learning as potential transdiagnostic protective factors following childhood violence exposure

Abstract: Childhood exposure to violence is strongly associated with psychopathology. High resting respiratory sinus arrhythmia (RSA) is associated with lower levels of psychopathology in children exposed to violence. High RSA may help to protect against psychopathology by facilitating fear extinction learning, allowing more flexible autonomic responses to learned threat and safety cues. In this study, 165 youth (79 female, aged 9–17; 86 exposed to violence) completed assessments of violence exposure, RSA, and psychopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 144 publications
1
5
0
1
Order By: Relevance
“…In addition, individuals with lower trait anxiety scores, lower depression scores as well as individuals exposed to childhood maltreatment were also non‐significantly overrepresented. These results are consistent with a recent study that reported a numerical overrepresentation of SCR non‐responder in youth exposed to childhood adversity (i.e., violence, threat) (Susman et al, 2021) and future studies should examine this in more detail. Indeed, we had hypothesized to observe blunted SCR and EMG responding (Iffland et al, 2014a; McLaughlin et al, 2015; McTeague & Lang, 2012) in individuals exposed to life adversity and had hence expected a link between responsiveness and exposure.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, individuals with lower trait anxiety scores, lower depression scores as well as individuals exposed to childhood maltreatment were also non‐significantly overrepresented. These results are consistent with a recent study that reported a numerical overrepresentation of SCR non‐responder in youth exposed to childhood adversity (i.e., violence, threat) (Susman et al, 2021) and future studies should examine this in more detail. Indeed, we had hypothesized to observe blunted SCR and EMG responding (Iffland et al, 2014a; McLaughlin et al, 2015; McTeague & Lang, 2012) in individuals exposed to life adversity and had hence expected a link between responsiveness and exposure.…”
Section: Discussionsupporting
confidence: 92%
“…We acknowledge that despite our hypothesis (based on e.g., (Jovanovic et al, 2009; Scharfenort et al, 2016; Stout et al, 2021)), also reports of increased psychophysiological reactivity can be found in the literature in adults (Stout et al, 2021), adolescents (SCR) (Cushman et al, 2021) as well as children (Giuliano et al, 2018) exposed to recent stressful life events. In addition, a recent study found higher sympathetic nervous system (respiratory sinus arrhythmia) reactivity to be associated with increases in transdiagnostic psychopathology (Susman et al, 2021). Hence, our results add to the literature by providing support for activating effects of recent adversity in adulthood on the sympathetic nervous system as indexed by SCRs as a proxy.…”
Section: Discussionmentioning
confidence: 99%
“…These unexpected findings may indicate that witnessing violence and hostility in one's home may not always lead directly to behaviorally learned violence, but rather produce a multitude of outcomes based on factors such as the child's individual qualities or coping mechanisms. Regarding individual differences that may differentially protect children, Susman et al (2021) found that there is variability across individuals' autonomic responses to learned threat and safety cues, with some individuals better able to regulate their responses to situations that may have otherwise elicited a violent response based on socially learned violence in the home. Further, it is not uncommon for youth to respond to home hostility with adaptively avoidant coping strategies that create patterns of conflict avoidance, distraction, or passivity rather than violence that may also carry over to the school and other domains (Allen et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the included studies leverage longitudinal designs, thereby strengthening inferences that variations in caregiving behaviors may impact trajectories of learning over time, particularly related to safety. The studies examined a wide variety of both adverse and positive caregiving behaviors INTRODUCTION ranging from maternal deprivation (Zanta et al, 2021); childhood violence exposure, including violence in the home (Susman et al, 2021); criticism, hostility, and emotional overinvolvement (Mullins et al, 2021); to everyday caregiving behaviors like explicit teaching (Aktar et al, 2022) and maternal engagement (Thrasher et al, 2021). Importantly, the impacts of caregiving on behavior and neurophysiological function were evident not only for the most severe forms of caregiving behaviors but across the full spectrum of caregiving.…”
mentioning
confidence: 99%
“…Turning next to resilience, Susman et al. (2021) tested 9–17‐year‐old youth with a history of childhood violence exposure to examine potential psychobiological protective factors against the development of psychopathology. Leveraging a longitudinal design coupled with an extinction learning paradigm, authors observed that the association between childhood violence exposure and later post‐traumatic stress disorder (PTSD) symptoms and externalizing problems was moderated by vagal tone, an index of regulatory function.…”
mentioning
confidence: 99%